Gaia white dwarfs within 40 pc - I. Spectroscopic observations of new candidates - Tremblay, Pier-Emmanuel; Hollands, M. A.; Fusillo, N. P. Gentile; McCleery, J.; Izquierdo, P.; Gaensicke, B. T.; Cukanovaite, E.; Koester, D.; Brown, W. R.; Charpinet, S.; Cunningham, T.; Farihi, J.; et al. (Monthly notices of the Royal Astronomical Society, 2020)
We present a spectroscopic survey of 230 white dwarf candidates within 40 pc of the Sun from the William Herschel Telescope and Gran Telescopio Canarias. All candidates were selected from Gaia Data Release 2 (DR2) and in almost all cases, had no prior spectroscopic classifications. We find a total of 191 confirmed white dwarfs and 39 main-sequence star contaminants. The majority of stellar remnants in the sample are relatively cool (< T-eff > = 6200 K), showing either hydrogen Balmer lines or a featureless spectrum, corresponding to 89 DA and 76 DC white dwarfs, respectively. We also recover two DBA white dwarfs and 9-10 magnetic remnants. We find two carbon-bearing DQ stars and 14 new metal-rich white dwarfs. This includes the possible detection of the first ultra-cool white dwarf with metal lines. We describe three DZ stars for which we find at least four different metal species, including one that is strongly Fe- and Ni-rich, indicative of the accretion of a planetesimal with core-Earth composition. We find one extremely massive (1.31 +/- 0.01 M-circle dot) DA white dwarf showing weak Balmer lines, possibly indicating stellar magnetism. Another white dwarf shows strong Balmer line emission but no infrared excess, suggesting a low-mass sub-stellar companion. A high spectroscopic completeness (>99 per cent) has now been reached for Gaia DR2 sources within 40-pc sample, in the Northern hemisphere (delta > 0 degrees) and located on the white dwarf cooling track in the Hertzsprung-Russell diagram. A statistical study of the full northern sample is presented in a companion paper.
Gesehen am 11.02.2021